2015
DOI: 10.1093/nar/gkv1377
|View full text |Cite
|
Sign up to set email alerts
|

Locking-to-unlocking system is an efficient strategy to design DNA/silver nanoclusters (AgNCs) probe for human miRNAs

Abstract: MicroRNAs (miRNAs), small non-coding RNA molecules, are important biomarkers for research and medical purposes. Here, we describe the development of a fast and simple method using highly fluorescent oligonucleotide-silver nanocluster probes (DNA/AgNCs) to efficiently detect specific miRNAs. Due to the great sequence diversity of miRNAs in humans and other organisms, a uniform strategy for miRNA detection is attractive. The concept presented is an oligonucleotide-based locking-to-unlocking system that can be en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 42 publications
(50 reference statements)
0
40
0
Order By: Relevance
“…Similar to DNA/AgNC miRNA sensors ( 48 ), our method is faster and easier than traditional miRNA quantification methods. The northern blot assay requires a long, labor-intensive protocol handling radioactive probes (radiolabeled) or expensive DIG-labeled LNA probes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to DNA/AgNC miRNA sensors ( 48 ), our method is faster and easier than traditional miRNA quantification methods. The northern blot assay requires a long, labor-intensive protocol handling radioactive probes (radiolabeled) or expensive DIG-labeled LNA probes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it could be used to estimate the average absolute concentrations of miRNAs in cells. This approach has been used previously for DNA/AgNC miRNA sensors ( 48 ), and here we used a similar approach to estimate 33 723–38 541 copies of miR122 per Huh7 cell. Our estimation is similar but higher than the previously reported copy number of miR122 in a Huh7 (∼16 000 copies), which was estimated by an RNase protection assay ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most widely used motifs is the molecular beacon [36] (Fig. 2c) Cytosine-rich sequences can be selected which stabilize silver nanoclusters, hence triggering their fluorescent emission [37] (Fig. 2d).…”
Section: Dna-based Optical Switchesmentioning
confidence: 99%
“…Reproduced with permission from refs. [2] (Copyright 2017 American Chemical Society), [36] (Copyright 1999 NationalAcademy of Sciences),[37] and[38].field of mechanochromic materials, which display an optical response to mechanical stimuli[39]. The optical signal can come from changes in absorption, emission or reflection of light, as the result of variations in the chemical or physical properties of the material and its integrated features.…”
mentioning
confidence: 99%
“…[9][10][11] Nowadays, different noble metal (such as Ag, Au, Pt, and Cu) NCs have been reported. 6,12 Among these metal clusters, DNA-stabilized silver nanoclusters (DNA AgNCs) have received particular attention because they are highly biocompatible and have been applied in the detection of DNA/ RNA, [13][14][15][16][17][18] sensing of small molecules 19 and bioimaging [20][21][22] studies. Recent studies have indicated that the emission color of AgNCs is controlled by multiple factors, including the number of silver atoms, 23 the shape of silver clusters, 24 the oxidization states of the silver atom, 25,26 the conformation of deoxyribose 27 and the silver-base interaction.…”
Section: Introductionmentioning
confidence: 99%